Potency of Wild Boar as Plant Pests in South Sulawesi - Fatmawaty, Andi St; Arif Bijaksana, Andi Muhammad (Universitas Gadjah Mada, 2024)
Land damage and the risk of crop failure caused by wild boar (Sus scrofa) is one of the main obstacles in producing agricultural products. Wild boars often attack agricultural crops when they are about to harvest, one of which is the damage to corn farms in several areas in Sulawesi which results in losses for corn farmers. Controlling this pest must be done quickly and precisely to create a safe agricultural environment. This study aims to determine the potential of wild boar as a plant pest, especially on agricultural land in South Sulawesi. The research was conducted in Mamasa, Bulukumba, and Bantaeng, South Sulawesi Province. Quantitative and qualitative methods were applied to obtain primary data by direct interviewing 63 respondents. Respondents were farmers who suffering from economic loss due to wild boar attacks on their crops, therefore, they were taken with purposive sampling and at random. Meanwhile, the secondary data were obtained from some related references. Results showed that the wild boar in South Sulawesi is a potential crop pests at areas of mountain (62%), swamp (38%) but not at bushland (0%). The most severe damaged crop was corn (70%), and the other damaged crops were cassava (11%), eggplant (6%), soybean (5%), tomato (3%), groundnut (3%), and sweet potato (2%). In order to reduce the pest risk, hence, extension program to educate the farmer community is needed.